Antioxidant Activity of Ethanol Extract Combination of Cavendis Banana Peel (Musa acuminata) and Kepok Banana Peel (Musa paradisiaca) Using the DPPH Method - Adriyan Suhada; Tuhfatul Ulya; Roushandy Asri Fardani; Ajeng Dian Pertiwi; Idham Halid; Pauzan Pauzan; Wulan Ratia Ratulangi; Nurul Indriani; Ni Nyoman Ariwidiani; Rosnalia Widyan; Evi Fatmi Utami; Wanda Novianty (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Banana peels, often considered agricultural waste, are rich in bioactive compounds with significant antioxidant potential. This study evaluates the antioxidant activity of a combined ethanol extract from Cavendis (Musa acuminata) and Kepok (Musa paradisiaca) banana peels using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay. The extraction was performed via maceration with 96% ethanol, yielding 9.13%. Phytochemical analysis identified key compounds including flavonoids, tannins, saponins, and steroids/terpenoids, which are known to exhibit antioxidant properties. The extract demonstrated strong radical scavenging activity with an IC50 of 6.47 ppm and an Antioxidant Activity Index (AAI) of 5.40, comparable to Vitamin C (IC50 = 6.29 ppm; AAI = 5.56). These results indicate a synergistic effect from combining the two banana peel varieties, enhancing antioxidant efficacy beyond that reported for individual peels. This study supports the potential use of Cavendis and Kepok banana peel extracts as sustainable natural antioxidants for application in food preservation, nutraceuticals, and cosmetics. Future work should focus on optimizing extraction methods, detailed phytochemical profiling, stability assessment, and in vivo validation to advance product development and maximize health benefits.